2014
DOI: 10.1016/j.lfs.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thiol antioxidant β-mercaptoethanol on diet-induced obese mice

Abstract: Aims Obesity and insulin resistance are associated with increased oxidant stress. However, treatments of obese subjects with different types of antioxidants often give mixed outcomes. In this work, we sought to determine if long-term supplementation of a thiol antioxidant, β-mercaptoethanol, to diet-induced obese mice may improve their health conditions. Main Methods Middle-age mice with pre-existing diet-induced obesity were provided with low concentration β-mercaptoethanol (BME) in drinking water for six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Because NAC was able to rescue oral cancer cell death induced by CYT‐Rx20, we tested whether two other thiol antioxidants, GSH and 2‐ME, had similar activity . Our results showed that CYT‐Rx20‐induced cytotoxicity was rescued in the presence of either GSH or 2‐ME (Figure A).…”
Section: Resultsmentioning
confidence: 94%
“…Because NAC was able to rescue oral cancer cell death induced by CYT‐Rx20, we tested whether two other thiol antioxidants, GSH and 2‐ME, had similar activity . Our results showed that CYT‐Rx20‐induced cytotoxicity was rescued in the presence of either GSH or 2‐ME (Figure A).…”
Section: Resultsmentioning
confidence: 94%
“…A role for ROS was further confirmed with the use of hydrogen peroxide (H2O2), an ROS-generating molecule [51]. The cells treated with H2O2 responded with an increased expression of CHOP, Zta, Ea-D, and cleaved caspase 3 (Figure 8A).…”
Section: Ros Are Involved In the Neo212-induced Lytic Cyclementioning
confidence: 81%
“…We investigated the potential role of ROS by including anti-oxidant compounds to suppress ROS production. C666.1 cells were treated with NEO212 in the presence or absence of ascorbic acid (AA) and beta-mercaptoethanol (BME), two well-known ROS scavengers [ 50 , 51 ]. Figure 8 A,B shows that NEO212 was neither able to potently stimulate CHOP expression nor trigger the lytic cycle when AA or BME were present in the cell culture medium, indicating the requirement of ROS for these processes.…”
Section: Resultsmentioning
confidence: 99%
“…However, pretreatment with p38 inhibitor SB203580 showed no significant effects ( Supplementary Figure 1D ). As NAC is a thiol antioxidant, we carried out further cytotoxicity experiments with the use of glutathione (GSH) and 2-mercaptoethanol (2-ME), two other thiol antioxidants [ 17 , 18 ], and the results showed that CYT-Rx20-induced cytotoxicity was largely reversed in the presence of either GSH or 2-ME ( Supplementary Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%